Comparison of soil compaction below wheels and tracks - Ansorge, Dirk (Cranfield University, 2005)
This study investigated the effect of high axle loads carried on self propelled wheels and tracks on soil bulk density, soil deformation, rut depth, and penetrometer resistance under controlled laboratory conditions. Furthermore pressure distribution below a three and a two idler track was measured. A brief field study was also conducted to compare the results gained under laboratory conditions. The benefit of the “Terra Trac” driving systems compared to wheel type systems was clearly shown in uniform and stratified soil conditions. Soil deformation was reduced to 50 % for the tracks compared to the wheels at an overall load of 12 t and 10.5 t, respectively. Penetrometer resistance showed a very high resistance close to the surface for the tracks. In uniform soil conditions there was no significant increase in penetrometer resistance compared to the control below 400 mm depth. Reducing the inflation pressure to half the recommended inflation pressure reduced soil deformation by 25 %. Three passes of a tire increased soil density by 20 % compared to a single pass. The three idler track showed only a 50 % increase in pressure from the front to the rear sprocket compared to a 100 % increase for the two idler track. Single peaks in pressure below each idler were less pronounced for the three idler track. Unfortunately the advantage in the pressure distribution for the three idler track did not lead to significant improved behavior concerning soil compaction. The advantage of a tracked combine compared to a wheeled combine is also shown in field measurements. The root system of oil seed rape in former track ruts is more developed than in former wheel ruts. Soil physical properties after the passage were compared to the predictions of two models. The tendency was correct, however the real values were largely offset.